Student Behavior Formation through Learning Physical Education, Sports, and Health at Madrasah Aliyah Hidayatul Mubtadi'in (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
Students lack discipline in participating in learning. This study aims to describe the role of physical education, sport, and health on the behavior formation of Madrasah Aliyah Hidayatul Mubtadi'in students, the role of learning physical education, sport, and health in cognitive, affective, and psychomotor formation in MA Hidayatul Mubtadi'in students. These factors influence behavior formation through learning physical education, sport, and health in Madrasah Aliyah Hidayatul Mubtadi'in students.This research is qualitative. In this study, the main subjects were students and physical education, sports, and health teachers. The research location is Madrasah Aliyah Hidayatul Mubtadi'in Bulusari, Sayung District, Demak Regency, Central Java Province. Data collection techniques using observation, interviews, and documentation. Data analysis used data reduction, data display, and conclusion/verification. The study results include the formation of attitudes through physical education, sport, and health, which can form honesty, discipline, care, respect, cooperation, responsibility. The role of physical education, sport, and health learning in the formation of cognitive, affective, and psychomotor application of learning includes three domains, the cognitive, affective, and psychomotor domains. These three domains are very important for students. Two factors influence student behavior: internal factors within oneself, such as instinct, belief, and conscience desire. In addition, there are also external factors such as the environment, home and school, and association with friends. The conclusion of this study is the contribution of physical education and sports in the formation of student behavior, among others, as follows to build honesty, strengthen discipline, encourage hard work, build responsibility, build cooperation, develop a fair and wise attitude. Physical education includes three important aspects, namely cognitive, psychomotor and affective. The factors that play an important role in human behavior are internal and external.